2022
DOI: 10.1186/s12884-022-05016-z
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of the predictors of completion of the continuum of maternity care in Ethiopia; using the recent 2019 Ethiopia mini demographic and health survey

Abstract: Background Despite the significant benefit of the continuum of care to avert maternal and neonatal mortality and morbidity, still the dropout from the continuum of care remains high and continued to become a challenge in Ethiopia. Therefore, this study aimed to assess the level of completion along the continuum of maternity care and its predictors among reproductive-age women in Ethiopia. Methods A secondary data analysis was done using the 2019 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Conversely, women in the 40–44 age group had lower odds of dropout from institutional delivery compared to their younger counterparts (15–19 years). This pattern is corroborated by studies in Ethiopia [ 29 ] and Mozambique [ 21 ]. This report could be associated with an increase in knowledge and decision-making abilities as women age [ 30 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Conversely, women in the 40–44 age group had lower odds of dropout from institutional delivery compared to their younger counterparts (15–19 years). This pattern is corroborated by studies in Ethiopia [ 29 ] and Mozambique [ 21 ]. This report could be associated with an increase in knowledge and decision-making abilities as women age [ 30 ].…”
Section: Discussionsupporting
confidence: 80%
“…A study in Colombia showed 95% of women were dropouts. Similarly, in Ethiopia, the proportion of women experiencing CoC dropout was reported at 87.1% [ 21 ]. Only about 10.7% Ugandan women received complete CoC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multilevel model was fitted at each model stage (model-I, model-II model-III and model-IV) to evaluate enumeration area cluster dependencies in prediction of maternity continuum of care. Model-I is the empty model i.e., intercept only terms, model-II is the individual only term, model-III comprises of the community term while model-IV combined all the terms as a full model 48 , 49 . The individuals (postpartum women) within households are nested in communities’ enumeration area cluster.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the ICC measured the degree of clustering based on heterogeneity between clusters i.e., the proportion of total variation in maternity CoC attributable to the community level random-effect component which can be expressed as: where is the between cluster variance (community random-component) and is the within community cluster variance from assumed normally distributed population 49 , 50 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation